Highly Crystalline MoS2 Thin Films Fabricated by Sulfurization. Issue 12 (4th November 2019) - Hutar, Peter; Spankova, Marianna; Sojkova, Michaela; Dobrocka, Edmund; Vegso, Karol; Hagara, Jakub; Halahovets, Yuriy; Majkova, Eva; Siffalovic, Peter; Hulman, Martin
Abstract : The 2D transition metal dichalcogenides attract high research interest due to their electronic properties, and MoS2 is likely the most explored compound of this group. The fabrication of MoS2 thin films by the sulfurization of predeposited MoO3 layers on a c‐plane sapphire substrate by radio frequency magnetron sputtering from stoichiometric MoO3 target is reported. The structure and properties of as‐grown MoO3 and MoS2 layers are characterized by several methods including X‐ray diffraction, grazing‐incidence wide‐angle X‐ray scattering, photoelectron spectroscopy, Raman spectroscopy, and atomic force microscopy. Furthermore, the influence of the crystallographic structure of MoO3 layers on the final MoS2 films is studied. The influence of the crystallographic structure of MoO3 on the resulting MoS2 films is focused. A strong texturation in the c ‐axis direction and an indication of a high degree in‐plane orientation of MoS2 thin films on the c‐sapphire substrate is observed. Abstract : Sulfurization of predeposited molybdenum oxide films is a suitable method for the fabrication of MoS2 on the wafer scale. The crystallographic orientation of MoS2 films can be tuned by appropriate crystalline substrate and sulfurization conditions. Highly crystalline MoS2 thin films prepared by the combination of radio frequency magnetron sputtering of MoO3 and a well‐established sulfurization process are shown.